2013
DOI: 10.1039/c2an36422k
|View full text |Cite
|
Sign up to set email alerts
|

Tattoo-based potentiometric ion-selective sensors for epidermal pH monitoring

Abstract: This article presents the fabrication and characterization of novel tattoo-based solid-contact ion-selective electrodes (ISEs) for non-invasive potentiometric monitoring of epidermal pH levels. The new fabrication approach combines commercially available temporary transfer tattoo paper with conventional screen printing and solid-contact polymer ISE methodologies. The resulting tattoo-based potentiometric sensors exhibit rapid and sensitive response to a wide range of pH changes with no carry-over effects. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
246
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(250 citation statements)
references
References 26 publications
2
246
1
1
Order By: Relevance
“…Tattoo based sensors have been widely developed [132] and used for different applications like as a potentiometric [133] and amperometric [134] sensor based systems. These devices have significant applications for skin worn silver (Ag) -zinc (Zn) alkaline batteries [135] and monitoring of change in pH [136] and ions like sodium and ammonium [137,138]. Chemical and biological sensing also involve pH measurements [139] by strapping the embedded system around the waist contained with the sensor connected with microcontrollers and LED.…”
Section: Sensor Network For Wearable Flexible Sensorsmentioning
confidence: 99%
“…Tattoo based sensors have been widely developed [132] and used for different applications like as a potentiometric [133] and amperometric [134] sensor based systems. These devices have significant applications for skin worn silver (Ag) -zinc (Zn) alkaline batteries [135] and monitoring of change in pH [136] and ions like sodium and ammonium [137,138]. Chemical and biological sensing also involve pH measurements [139] by strapping the embedded system around the waist contained with the sensor connected with microcontrollers and LED.…”
Section: Sensor Network For Wearable Flexible Sensorsmentioning
confidence: 99%
“…On the other hand, electrochemical methods are typically straightforward and inherently quantitative, and require simpler operation and setups. Electrochemical methods, however, have downsides, such as long-term instability and vulnerability to electrode fouling, but nevertheless, they are the most commonly used methods for pH detection, whereby the potential (potentiometric) [20,21,[51][52][53][54][55][56], current (amperometric) [57][58][59][60][61][62][63], or charge in an electrochemical cell serve as the analytical signals. Indeed, the glass electrode is currently the most commonly used electrochemical sensor for potentiometric pH measurements.…”
Section: Ph Sensing Mechanismmentioning
confidence: 99%
“…Flexible, stretchable, and transparent electronics that can be intimately associated with human skin and tissues is likely to play a significant role in future applications involving chemical sensing (236,(341)(342)(343)(344)(345). Currently, wearable sensors are mainly applied to the measurement of electrical activity produced by the brain and heart of humans noninvasively (342).…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
“…Recently, Windmiller et al (344) showed that on-skin tattoo electrodes can be fabricated and employed for electroanalytical measurements, though no real-time body-sensing measurements were reported. The combination of tattoo-based electrochemical sensors with wearable electronics may, in the future, assist with the realization of fully functional electronic skin (344,345). This is a most interesting and also challenging research subject, as, in principle, it may allow important parameters related to personal health to be continuously monitored in a noninvasive or minimally invasive manner (56).…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%